Content and Language Integrated Learning (CLIL) in a Medicine Program in Colombia: Results of a Perception Survey in Students - Rodolfo Adrián Cabrales Vega; Germán Alberto Moreno Gómez; Sebastián Arcila Ramírez (Universidad de La Sabana, 2022)
This study collected the perception of medical students about the use of English for teaching through the use of a strategy based in Content and Language Integrated Learning (CLIL) approach at Universidad Tecnológica de Pereira (UTP) Colombia. A descriptive observational quantitative research was conducted in a group of 128 students of medicine who agreed to participate in the strategy called "Strategy for Paper's Bilingual Presentation (SPBP)" in the subjects of Surgical Clinic I and II. Of this group, 98.5% (126) considered learning English important in their training and 86% (110) essential to advance without difficulties in their studies. In addition, there was a 52.3% (67) of students who stated that the University should foster the use of English integrated with contents in specific programs. In reference to the teaching of English at the University, 85.9% (110) of the students considered that it should be integrated into the content of the academic programs. The didactic strategy was positively evaluated by 86.7% (111), and 61% (78) used English exclusively or preferentially. Scenic fear and lack of knowledge of technical language were arguments for the preferential use of Spanish in the session. Among the recommendations made by the students were the extension of the preparation time for the activity, the inclusion of clinical cases, and the selection of the assigned topics with the teacher. The didactic strategy used proved to be very useful and replicable in other semesters and training levels of the Medicine program. It is imperative to design and promote bilingual spaces that allow the use of English as a strategy to integrate contents and language in the teaching of Medicine.